Chinese Students' Evaluative Reactions to Hong Kong English - Li, Shengnan; Ting, Su Hie; Qin, Limin (2021)
The purpose of this research was to elicit experimentally evaluative reactions to female and male Hong Kong English speakers among China university students by using “verbalguise technique”. Two one-minute recordings depicting a plan of the underground facilities of a museum were recorded by two speakers in their own words. 30 English major students from a university in Shandong Province of China rated the two recordings on the bipolar semantic scale with 16 adjectives. Data analysis shows that the evaluation of male recorder overally is higher than that of female recorder. The students gave more positive evaluations to the speaker of the same sex as themselves